Effect Of Crude Seed Extract Of Some Indigenous Plants For The Control Of Legume Pod Borer (Maruca Vitrata F.) On Country Bean - Rouf, FMA; Sardar, MA (Bangladesh Journal of Agricultural Research, 2011)
The crude seed extract of neem, black pepper, mahogani, and garlic bulb with three doses were evaluated against legume pod borer in the country bean field in two seasons kharif 2006 and rabi 2006-2007. The neem seed extract applied @150 and 100 g/l and mahogani seed extract @ 100 g/l of water 7 days intervals on the country bean showed better performance in the reduction of flower and pod damage with significantly higher yield of bean in both the seasons. The seed extracts lost the efficacy against legume pod borer after 7 days of application. Keywords: Indigenous plant materials; crude extract; country bean; legume pod borer. DOI: http://dx.doi.org/10.3329/bjar.v36i1.9228 BJAR 2011; 36(1): 41-50